Metal complexation, FT-IR characterization, and plankton abundance in the marine surface microlayer of coastal areas in the Eastern Mediterranean - Karavoltsos, Sotirios; Sakellari, Aikaterini; Plavšić, Marta; Bekiaris, Georgios; Tagkouli, Dimitra; Triantafyllidis, Anastasios; Giannakourou, Antonia; Zervoudaki, Soultana; Gkikopoulos, Ioannis; Kalogeropoulos, Nick (Frontiers in Marine Science, 2022)
Barely any data exist on metal speciation in the marine surface microlayer (SML), a rather complex environment, the study of which contributes to enhancement of knowledge on metal speciation and its effect to the ocean. Metal speciation is significant since life requires a wide variety of trace metals that are essential for the growth of the organisms. Ligand concentrations (L) of copper (Cu), zinc (Zn), and cadmium (Cd) were studied by anodic stripping voltammetry (ASV) in the SML of coastal areas within the Aegean Sea in the Eastern Mediterranean. Complexing capacities in the SML in decreasing order ranged for Cu from 29 to 201 nM (median 101 nM), for Zn 24–149 nM (45 nM), and for Cd 1.0–1.5 nM (1.4 nM). Average enrichment factors (EFs) of SML samples compared to subsurface ones (SSW) were calculated equal to 0.9 ± 0.8, 1.2 ± 0.5, and 1.7 ± 1.6 for LZn, LCu, and LCd, respectively. In five out of the six total paired samples of SML and SSW, lower concentrations of LZn were measured in the SML, which is not the case for LCu and LCd. Due to elevated dissolved Zn concentrations in the SML, its complexation is incomplete, contrary to those of Cu and Cd, which are fully complexed. These trace metals are essential nutrients for biological functions, hence any differences on their concentration and chemical speciation may directly influence the distribution of phytoplankton species in the upper water column and neuston. EFs of SML relatively to subsurface water ranged in average between 1.2 and 2.4 for total organic carbon (TOC), chlorophyll a (Chla), and plankton, being generally >2 for most of the amino acids detected, demonstrating a relative enrichment of the SML in organic matter. A significant correlation was found between Cu ligands and dinoflagellates <20 μm, confirming older findings supporting that marine dinoflagellates of Gymnodinium genera produce Cu ligands. New insights are provided in the study and the importance of investigating bio-essential metal ions (Cu, Zn, Cd) and their organic complexes in the SML is pointed. Data on Zn and Cd complexing capacities in the SML are the first published so far.